A roadmap for island biology: 50 fundamental questions after 50 years of The Theory of Island Biogeography. - Patiño, J; Whittaker, R; Borges, P; Fernández-Palacios, J; Ah-Peng, C; Araújo, M; Ávila, S; Cardoso, P; Cornuault, J; de Boer, E; de Nascimento, L; Gil, A; et al. (Wiley, 2017)
Aims The 50th anniversary of the publication of the seminal book, The Theory of Island Biogeography, by Robert H. MacArthur and Edward O. Wilson is a timely moment to review and identify key research foci that could advance island biology. Here we take a collaborative horizon-scanning approach to identify 50 fundamental questions for the continued development of the field. Location Worldwide. Methods We adapted a well-established methodology of horizon scanning to identify priority research questions in island biology, and initiated it during the Island Biology 2016 conference held in the Azores. A multidisciplinary working group prepared an initial pool of 187 questions. A series of online surveys was then used to refine a list of the 50 top priority questions. The final shortlist was restricted to questions with a broad conceptual scope, and which should be answerable through achievable research approaches. Results Questions were structured around four broad and partially overlapping island topics, including: (Macro)Ecology and Biogeography, (Macro)Evolution, Community Ecology, and Conservation and Management. These topics were then subdivided according to the following subject areas: global diversity patterns (5 questions in total); island ontogeny and past climate change (4); island rules and syndromes (3); island biogeography theory (4); immigration–speciation–extinction dynamics (5); speciation and diversification (4); dispersal and colonization (3); community assembly (6); biotic interactions (2); global change (5); conservation and management policies (5); and invasive alien species (4). Main conclusions Collectively, this cross-disciplinary set of topics covering the 50 fundamental questions has the potential to stimulate and guide future research in island biology. By covering fields ranging from biogeography, community ecology, and evolution to global change, this horizon scan has the potential to foster the formation of interdisciplinary research networks, enhancing joint efforts to better understand past, present and future of island biotas.